Mutual fund performance when parent firms simultaneously manage hedge funds - Cici, Gjergji; Gibson, Scott; Moussawi, Rabih (Journal of Financial Intermediation, 2010)
This study examines the performance of mutual funds managed by firms that simultaneously manage hedge funds. We find that the reported returns of mutual funds in these “side-by-side” associations with hedge funds significantly underperformed those of mutual funds that shared similar fund and family characteristics but differed in that they were not affiliated with hedge funds. Digging deeper into performance, we find that the underperformance was confined to return gaps, a return measure that captures the impact of unobservable managerial actions. Interestingly, mutual funds with investment styles that were most closely aligned to affiliated hedge funds generated reported-return alphas and return gaps that underperformed by the greatest amount. Finally, we find that side-by-side mutual funds received less of a contribution to performance from IPO underpricing than similar unaffiliated mutual funds or affiliated hedge funds. Evidence does not support the hypothesis that affiliations with hedge funds allow side-by-side mutual funds to attract superior stock-picking talent. Our evidence does not allow us to rule out the possibility that management firms maximized fee income by strategically transferring performance from mutual funds to hedge funds.